Pola Arus Permukaan dan Kondisi Fisika Perairan di Sekitar Pulau Selayar pada Musim Peralihan 1 dan Musim Timur - Ahmad Bayhaqi; Mochamad Riza Iskandar; Dewi Surinati (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Surface Current Pattern and Physics Condition of Waters Around Selayar Island in the First Transitional and Southeast Monsoons. Seasonal observations of the flow of surface water and physics conditions around Selayar Island adjacent to Arlindo throughflow pathways of Makassar Strait have been conducted with a focus on the first transitional season and the southeast monsoon season. The purpose of this research is to obtain the pattern of seasonal surface current and physics characteristics of water column, i.e. temperature and salinity in Selayar Island waters during those seasons. The observations conducted on 22–27 May 2015 and 7–10 August 2015 illustrated the successive periods of the first transitional season and the southeast monsoon season. The methods used for taking oceanographic data such as temperature, salinity, and current were the stationary oceanographic measurement using CTD and currentmeter at 29 stations located in surrounding waters of Selayar Island. The surface current pattern generated from the interpolation process of the overall observation stations indicated that during the first transitional season the current moved eastward with an average velocity of 0.25 m/s. During the southeast monsoon season, the same pattern was still observed with a slightly higher average velocity of 0.26 m/s. The temperatures and salinity of Selayar Island waters during the southeast monsoon season were 2°C lower and 0.5 psu higher than during the first transitional season. Differences in mean current velocity values tended to be more affected by local tidal conditions. Different salinity was thought to be influenced by upwelling phenomena and local climatic factors such as rainfall, wind, and river flow discharge.